STUDI FENOMENOLOGI KECURANGAN MAHASISWA DALAM PELAPORAN PERTANGGUNGJAWABAN DANA KEGIATAN MAHASISWA: SEBUAH REALITA DAN PENGAKUAN - Cahyaningtyas, Ruri Ihsania (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research background is the indication of fraudulent practices in educational environment which are conducted by students in Accountability Reporting (LPJ) of student activity funds. The purpose of this study is determining and provide an overview of that fraud in Economics and Business Faculty, Brawijaya University (FEB UB) based on each informant’s experiences. Phenomenology is used as a method to find informant's understanding and awareness about fraud that conducted by students in LPJ, by using data analysis model Transcedental Husserl. This study's findings indicate that kind of fraud done by students are the forgery of signatures and transaction evidence, mark up / mark down, and misappropriation of activity funds. The cause of fraud explained using the perspective of Fraud Pentagon theory, conducting of arrogance; competency; opportunity; pressure; and rationalization, in which religion is a bulwark for students to prevent fraud in LPJ. It takes good cooperation of various parties, not only the students but also the Deanery and the goverment, in oder to strive for changes in Accountability Reporting of students activities funds system to ensure that students will not hesitate to revealing LPJ according to actual conditions that occured. Keywords: Student’s Fraud, The Accountability Reporting of Student Activity Fund, Phenomenology.